Indonesian Upstream Oil & Gas Governance for Sustainable Innovation - Mohamad Firwan Aprizal; Bambang Juanda; Anny Ratnawati; Abdul Muin (Jurnal Manajemen dan Organisasi, 2022)
Indonesian oil reserves and production are greatly influenced by investment. The focus of the study is to evaluate governance options to boost investment through appropriate fiscal regime and non-fiscal policies. The main aspect of the fiscal regime to increase investment is cost recovery. When cost recovery is still interpreted as a burden on state finances and there is still a stigma that contractors commit fraud in cost recovery, it is then a big challenge for oil and gas contractors to maximize investment and for regulator in giving approval on budget. Flexible Split and First Trance Petroleum (FTP) are the 2nd highest priority to improve to accommodate dynamic situation on the oil industry such as oil price fluctuation and size of reserves. Incentives and windfall profit treatment are the other key issues on fiscal. Sufficient geological surveys and researches are crucial things to attract investment. The duration of a contract that is only 30 years is too short to maximize the contractors return because of lengthy period for exploration, construction and drillings prior production. Combination of NOC dominated and Separation of Power model seems to be the best governance model. Partnership between Pertamina and multi-national company will facilitate investment funding.